The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1097/00005537-200303000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment and Tinnitus Pitch in Patients With Unilateral Tinnitus: Comparison of Sudden Hearing Loss and Chronic Tinnitus

Abstract: The results suggest that tinnitus is related to hearing impairment in the same frequency region in patients with sudden sensorineural hearing loss with tinnitus or in patients with chronic tinnitus, whereas some instances of chronic tinnitus are caused by reorganization in cortical cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 20 publications
5
32
1
1
Order By: Relevance
“…These findings support the suggestion that damage to cochlear hair cells plays a crucial role in the pathogenesis of tinnitus [3]. …”
Section: Introductionsupporting
confidence: 90%
“…These findings support the suggestion that damage to cochlear hair cells plays a crucial role in the pathogenesis of tinnitus [3]. …”
Section: Introductionsupporting
confidence: 90%
“…[1][2][3] The severity of tinnitus commonly increases with the degree of hearing loss, and the pitch of tinnitus often coincides with the frequency of the lesion or is just below the precipitous edge of the lesion. 4,5 These findings demonstrate that damage to cochlear hair cells plays a crucial role in the pathogenesis of tinnitus. The decreased signal transduction from damaged hair cells may result in a reduction of lateral inhibition at the dorsal cochlear nucleus or inferior colliculus into a characteristic frequency, followed by the development of hyperactivity in auditory neurons at the edge of the frequency.…”
Section: Introductionmentioning
confidence: 93%
“…Induction of tinnitus with a 1/3 octave band noise stimulus results in tinnitus frequency at the lower end of the range of loss (Atherley et al, 1968). In humans with unilateral highfrequency sensorineural hearing loss and tinnitus in the same ear, tinnitus frequency corresponds to the lower frequency edge of the range of the hearing loss (Ochi et al, 2003). Kiang et al (1970) suggested that the tonotopic profile of SA in auditory nerve fibers might be a neural correlate of tinnitus.…”
Section: Relationship To Tinnitusmentioning
confidence: 99%